A modelagem no ensino e na aprendizagem de matemática nos primeiros anos do ensino fundamental - Marcão, Daniela Gervásio (2017)
The problem to which the research sought to answer was: What are the knowledge related to Mathematic Modeling that teachers need to master so that they can develop a pedagogical practice in Mathematics in the first years of Elementary Education that enables students to acquire truly meaningful learning? This research aimed to identify, analyze and systematize the main knowledge inherent from Modeling that contribute to the development of a pedagogical practice in the first years of Elementary School, in order to enable students to acquire significant learning of the contents of Mathematics. In order to answer the problem and to reach the proposed objectives a bibliographic research of the meta-analysis type was developed. In this sense, the study describes, analyzes and systematizes the main characteristics of Mathematics teaching, some alternative methodologies, the theories of learning under the Ausubel and Rogers approach, and a deep learning of the Modeling, object of the study, with the purpose of subsidizing the growing of Teachers who work directly in the first years of Elementary Education. Thus, the importance of working with Mathematical Modeling is one of the methodological trend of Mathematical Education capable of overcoming beliefs and conceiving a contextualized Mathematics teaching that stimulates the active participation of the students in order to provide meaningful learning and highlight the relevance of Mathematics to life.